INFILTRASI GERAKAN HIZBUT TAHRIR: Studi Terhadap Gerakan Hizbut Tahrir di Yogyakarta - Zulfadli, Zulfadli (Turast: Jurnal Penelitian dan Pengabdian, 2013)
The paper examines the infiltration of Hizbut Tahrir Indonesia’s movement. In the fact, HTI is one of movementswhich is regularly to establish the shariah as legal system of Indonesia. In addition, HTI has also been known asradical organization to establish it. In this context, the research concerns in understanding that pattern. Withqualitative method—descriptive analysis—the research can be expected to gather the data comprehensively. Onother hands, the study is located in D.I. Yogyakarta with some argumentations. Yogyakarta is a famous citywhich have number of huge students and HTI establish there massively. Essentially, the research shown thatHTI can be analyzed through some social theories like social movement, arena and symbolic power theories. Itcan be understood that HTI uses the politics opportunity—reformation moment—to finish the undergroundof movement; Next, mobilizing structure—internatal and external mobilization. Finally, managing themovement process—against the westernization.